ART BARONG ROLE IN IMPROVING PARTICIPATION IN PELEM VILLAGE DISTRICT BLORA - Rohmaniah, Siti Alfiatur (SOSIALITAS; Jurnal Ilmiah Pend. Sos Ant)
This research aims to: (1) determine the role of art in the Art Barong increase community participation Pelem Village, District Blora; (2) determine the strategy that needs to be done to preserve the arts at the Art Barong Pelem Village, District Blora; ( 3) determine the impact of art on society participation Barong Art Pelem Village, District Blora.This research used qualitative methods. This method was chosen because of qualitative research study of a phenomenon that occurs in a society that is described in detail by using certain methods in order to produce an answer to the question that is being studied in the research. This research is a case study of spikes, because this study to explain or interpret a case (case) in the context naturally, without the intervention of outside parties. Sources of data obtained from the literature, which includes archives and documents and village informants and community members in the village Pelem Barong Art. Data collection techniques used were observation, interview and documentation. The validity of the data obtained through triangulation or the triangulation of data sources. The data analysis technique used in this study is an interactive analysis model (interactive models of analysis) which includes 4 components namely (1) data collection, (2) data reduction, (3) presentation of data, (4) conclusion.Based on the results of the research it can be concluded that Art Barong improve community solidarity manifested by the increasing spirit of mutual cooperation and empathy within to preserve the art of barong made by all elements of society which includes governments, artists and art Barong.Seni open new jobs for the community, many people are good at reading opportunities with trinkets and accessories barongan. Barong art community lose faith in yourself, because every performance Barong Art synonymous with many people who sell liquor and gambling.Keyword: Solidarity society, Barong art preservation, New jobs, Lowering the faith community.